2016
DOI: 10.5265/jcogpsy.13.71
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phonological familiarity and number of mates on homophone processing in native Japanese readers

Abstract: Lexical decision times for homophones are usually longer than are those for nonhomophones, a phenomenon known as the homophone e ect. However, experimental results regarding lexical decision times for Japanese homophones with multiple mates were inconsistent. We considered that this inconsistency could be due to the variance in the phonological familiarity regarding the homophones. Accordingly, we measured the lexical decision times for Japanese homophones with multiple mates and for those with a single mate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Our findings of null effect, or at best a trend of advantage regarding homophone processing in Japanese, weakly echoed the reported advantage in processing multi-mate homophones (Hino et al, 2013), but challenged the findings of a disadvantage in visual processing (Tamaoka, 2007;Mizuno & Matsui, 2016). Similar to the situation in Mandarin, the existing inconsistencies regarding homophone effects in visual word processing prevents us from any conclusive argument within Japanese.…”
Section: Figure 2 Effect Of Each Additional Meaning In Japanese Mansupporting
confidence: 49%
See 1 more Smart Citation
“…Our findings of null effect, or at best a trend of advantage regarding homophone processing in Japanese, weakly echoed the reported advantage in processing multi-mate homophones (Hino et al, 2013), but challenged the findings of a disadvantage in visual processing (Tamaoka, 2007;Mizuno & Matsui, 2016). Similar to the situation in Mandarin, the existing inconsistencies regarding homophone effects in visual word processing prevents us from any conclusive argument within Japanese.…”
Section: Figure 2 Effect Of Each Additional Meaning In Japanese Mansupporting
confidence: 49%
“…For example, while Tamaoka (2007) reported a homophone disadvantage in Japanese similar to that found in English within both visual lexical decision and word naming tasks, Hino and colleagues (2013) reported that such a disadvantage was limited to mono-mate homophones, and for homophones with more than one mate, participants, on the contrary, responded faster than they did for mono-meanings words. However, a recent study by Mizuno and Matsui (2016) challenged the findings by Hino and colleagues, showing that homophones in general had longer response latencies than monomeaning words, and multi-mate homophones had even longer latencies than single-mate homophones. Such inconsistencies also hold within Mandarin.…”
Section: Homophone Processing In An Auditory Lexical Decision Taskmentioning
confidence: 81%
“…Even, differences in the character type of words can differ the time required to understand by over 110ms [44]. The number of homophones also affects word judgment time by tens of milliseconds [45]. Therefore, differences in the converted character strings may have caused variations in KKCCT around tens to hundreds of milliseconds.…”
Section: Potential Causes Of Variations In Kkcctmentioning
confidence: 99%